DEVELOPMENT OF E-MODULE BASED STEM EDP ON ELEMENTARY SCHOOL STUDENT'S LEARNING PROCESS - Siti Nurmandayanti; Astri Sutisnawati; Din Azwar Uswatun (Jurnal Cakrawala Pendas, 2025)
This study aims to develop and determine the feasibility and effectiveness of a STEM (Science, Technology, Engineering, and Mathematics)-based e-module using the Engineering Design Process (EDP) approach in elementary science learning. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analyze (identifying needs and student characteristics), Design (designing the structure and content of the e-module), Develop (developing the digital product and conducting expert validation), Implement (testing with fifth-grade students at SDN Gunung Parang, Sukabumi City), and Evaluate (analyzing effectiveness through pre-test, post-test, and student response questionnaires). The subjects were 21 fifth-grade students. Data were collected through interviews, questionnaires, expert validations (material, media, and practitioners), and learning achievement tests. Validation results showed an overall feasibility score of 88% (very feasible), with 79% from material experts, 90% from media experts, and 95% from practitioners. Effectiveness testing indicated an increase in students’ average scores from 59.38 (pre-test) to 90.00 (post-test), with an N-Gain value of 0.75 (high category). Therefore, the STEM–EDP-based e-module is declared feasible and effective for improving students’ conceptual understanding and critical thinking skills on the topic Light and Its Properties, serving as an innovative alternative learning medium for elementary science education.